Dual-Piezo-Charge Strategy in (1–0)–3 Single-Crystal Composite for Enhancing Underwater Acoustic Sensing - Lei, Yu; Li, Xiaotian; Hou, Zewei; Wang, Bing; Zheng, Shuguang; Wei, Yang; Yu, Zhonghui; Hong, Jiawang; Dong, Shuxiang (Nano-Micro Letters, 2026)
Piezoelectric ultrasonic transducers (PUTs) are extensively used in diverse technological fields, yet further enhancement in acoustic sensitivity and hydrostatic figure of merit dhgh have plateaued in conventional 1–3 piezocomposites, whose structures have remained largely unchanged for decades. Herein, we report a (1–0)–3 single-crystal piezocomposite (SCPC) based on the [011]-oriented Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 (PIN-PMN-PT) single-crystal, featuring a dual-piezo-charge (DPC) mechanism arising from the piezoelectric and piezoelectret synergy effect. The ordered and polar 0-phase microholes with aligned dipoles are intentionally introduced in 1-phase piezo-pillars, yielding a uniquely low effective dielectric constant, reduced acoustic impedance, and DPC properties unattainable in conventional SCPCs. Both Simulations and experiments confirm that this DPC mechanism in (1–0)–3 SCPC enables an ultrahigh dhgh of 8089 × 10−15 m2 N−1, representing increases of 443.2% and 890.6% over commercial 1–3 SCPC and 1–3 piezoceramic composite, respectively. The engineered microhole structure and DPC strategy also significantly enhance underwater acoustic sensitivity while maintaining a broad − 3 dB bandwidth of 130 kHz, crucial for maritime safety and collision avoidance. Meanwhile, the long-term testing further verifies the PUT’s operational stability. This design approach offers a promising pathway for next-generation piezocomposites and PUT technologies. Highlights: 1 (1–0)–3 single-crystal piezocomposite (SCPC) based on [011]-oriented relaxor PIN-PMN-PT crystal was fabricated via a modified method combining 3D printing-assisted dice-and-insert with dice-and-fill techniques. 2 The (1–0)–3 SCPC, characterized by ordered and poled microholes and incorporating a dual-piezo-charge mechanism, achieves an ultrahigh hydrostatic figure of merit dhgh of about 8089 × 10−15 m2 N−1. 3 The ultrasound transducer based on (1–0)–3 SCPC exhibits a 70% enhancement in underwater acoustic sensitivity while maintaining a broad − 3 dB bandwidth of 130 kHz.